Synthesizing The Evidence: TP53 Mutations as a Prognostic and Predictive Biomarker in Breast Cancer - Laila Chuvita; Syifa Sofia Wibowo (Medical and Health Journal, 2026)
The journey to personalize breast cancer therapy increasingly navigates the complex landscape of somatic TP53 mutations, the most frequent genetic drivers of this disease. Moving beyond a simple prognostic badge, we now understand these mutations create a spectrum of clinical behaviors, deeply influenced by their specific functional impact and, critically, by their genetic companions. A systematic literature review was conducted across three major electronic databases: ScienceDirect, ProQuest, and Scopus. The search was restricted to peer-reviewed journal articles published in English between 2021 and 2024 to ensure the inclusion of recent evidence. The confluence of TP53 and PIK3CA mutations stands out as a devastating synergy that heralds a tumor phenotype with profound resistance to common chemotherapy regimens, especially taxanes, and the direst survival outcomes. This genetic context also subtly reshapes responses to HER2-targeted drugs, revealing that TP53's influence is both powerful and context-dependent. A more nuanced profiling, one that accounts for these critical genetic interactions, is no longer a future aspiration but a present necessity. These findings collectively advocate for the integration of comprehensive molecular profiling, including nuanced TP53 and PIK3CA assessment, into clinical decision-making.